2019
DOI: 10.1016/j.pedneo.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non- and under-vaccination among children aged 12–23 months in Malawi. A multinomial analysis of the population-based sample

Abstract: Background: Non-and under-vaccination among children in Malawi have received little attention. Between 2010 and 2016, the proportion of children who received full immunization before their first birthday dropped from 81% to 76% in Malawi. This signifies that a certain fraction of children are either non-vaccinated or under-vaccinated. Thus, the present study attempted to examine the predictors of non-and under-vaccination among children aged 12 e23 months in Malawi. Methods: Cross-sectional data obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 27 publications
8
55
1
Order By: Relevance
“…Family size was associated with the probability of a child being fully immunized. It was revealed that children from large families have low vaccine uptakes, considering the burden of other children at home in taking up immunization services [11,13,25,46,50]. Migration was also cited as a hindrance to childhood immunization coverage [30,35,44,48].…”
Section: Resultsmentioning
confidence: 99%
“…Family size was associated with the probability of a child being fully immunized. It was revealed that children from large families have low vaccine uptakes, considering the burden of other children at home in taking up immunization services [11,13,25,46,50]. Migration was also cited as a hindrance to childhood immunization coverage [30,35,44,48].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight articles met all inclusion criteria for this study; 28 articles were excluded for various reasons. [See supplementary materials 3] Nine articles employed second-hand data analysis [7,12,18,27,37,40,41,47,42]; thirty-six used crosssectional design [1][2][3]11,[13][14][15][16][17]19,[21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][38][39]42,[45][46][48][49][50][51]53,54] and three used case-control study [20,[43][44]. All described studies were conducted on Africa populations (103,655 adults and 76,327 children).…”
Section: Resultsmentioning
confidence: 99%
“…One critically examined barriers speci c to vaccination doses at birth 0 -1day [18] in the Gambia. Thirty articles reported national immunization coverage [1][2]7,[11][12][13][14][15][16][20][21][22][23][24][25][28][29]32,[34][35][38][39][40][43][44][45][46]49,50,[52][53][54], eighteen did not [3,[17][18][19]22,24,[26][27][30][31]33,[36][37][41][42]47,48,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations